Psychology in your life - Grison, Sarah; Gazzaniga, Michael S. (New York W. W. Norton & Company, 2019)
"Makes science accessible at all levels by showing how psychology is relevant to students' everyday lives. Author Sarah Grison--an expert in the teaching of introductory psychology--has created a print and digital package with an equal commitment to the success of every instructor and student. A strong, author-driven support package--rich with original media, a test bank, Active Learning slides, and InQuizitive adaptive learning modules--provides instructors with everything they need to help today's students understand and apply introductory psychology"--
Introducing the world of psychology : why is psychology important to you? -- The role of biology in psychology : how do our nervous systems affect thinking and behavior? -- Consciousness : what does it mean to be conscious? -- Development across the life span : how do we develop in the womb? -- Sensation and perception : how do sensation and perception affect us? -- Learning : what are the three ways we learn? -- Memory : how do we acquire memories? -- Thinking and intelligence : what is thinking? -- Motivation and emotion : what motivates our behavior? -- Sex, gender, and sexuality : how does biology make us male or female? -- Health and well-being : what affects our health? -- Social psychology : how do we think about other people? -- Self and personality : how do we know ourselves? -- Psychological disorders : what is a psychological disorder? -- Psychological treatments : how are psychological disorders treated?
Includes bibliographical references and index.
Keywords: Developmental psychology; Psychology